Mechanistic role of HPV-associated early proteins in cervical cancer: Molecular pathways and targeted therapeutic strategies - Bhattacharjee, Rahul; Das, Sabya Sachi; Biswal, Smruti Sudha; Nath, Arijit; Das, Debangshi; Basu, Asmita; Malik, Sumira; Kumar, Lamha; Kar, Sulagna; Singh, Sandeep Kumar; Upadhye, Vijay Jagdish; Iqbal, Danish; et al. (Critical reviews in oncology/hematology, 2022)
Cervical cancer (CC), one of the major causes of death of women throughout the world is primarily caused due to Human Papilloma Virus (HPV) 16 and 18. The early region (E) oncoproteins of HPV are associated with the etiopathogenesis and contribute to the progression of cancer. The present article comprehensively discussed the structural organization and biological functions of all E proteins of HPV and their contribution to progression of CC with an intent to decipher the pathological hallmarks and their relationship. Additionally, the role of E proteins in reference to therapeutics will also be presented. A systematic search has been carried out for articles published in PubMed database by using combinations of different keywords with Boolean operators (AND, OR, NOT) including cervical cancer, HPV, E proteins, and signaling. From the analysis of literature review, its apparent that E proteins are the major contributor to disease progression. E1, E2, and E4 forms are mainly associated with viral integration, replication, and transcription whereas E6 and E7 act as an oncoprotein and are associated with the progression of cancer. E5 regulates cell proliferation, apoptosis, and facilitates the activity of E6 and E7. Additionally, E proteins were observed associated with numerous cell signaling pathways including PI3K/AKT, Wnt, Notch and reasonably contribute to the initiation of malignancy, cell proliferation, metastasis, and drug resistance. Knowing the role and interplay of each protein in initiation to progression of CC, their therapeutic significance has been elucidated. The present study observations demonstrate that E6 and E7 are the major cause of HPV-mediated CC progression. E1, E2, and E5 also act as a backbone for E6 and E7 and most of the current approaches have targeted E6 and E7 mediated action only. The present review illustrates the structural organization as well as function and regulation of all early proteins of HPV and their association with several cellular signaling pathways. The observations provide clue on the regulatory aspect of these proteins in initiation to progression and reasonably represent that targeting these proteins could be a novel therapeutic strategy for CC. In particular, its seemingly appears that inhibition of the activity of E6 and E7 oncoproteins may be a better selective target to delay the progression of CC. The review reaffirms the role of E proteins and encourages future studies on developing diagnostics, and most importantly therapeutics strategies targeting E6 and E7 oncoproteins to tackle CC related morbidity and mortality. [Display omitted] •Human papillomavirus (HPV) has crucial role in cervical cancer (CC) progression.•Targeting E proteins leads to improved therapy in HPV-mediated CC.•Silencing HPV oncoproteins is a promising therapeutic strategy in CC therapy.•Targeted therapeutics and advanced diagnostic tools to enhance the treatment strategies of HPV-mediated CC.